(untitled) - Sauer, Markus (Weinheim, 2011)
Chapter 1: Absorption and Emission of Light; Spectroscopic Transition Strengths; Lambert–Beer Law and Absorption Spectroscopy; Fluorophore Dimerization and Isosbestic Points; Franck–Condon Principle; Temperature Effects on Absorption and Emission Spectra; Fluorescence and Competing Processes; Stokes Shift, Solvent Relaxation, and Solvatochroism; Fluorescence Quantum Yield and Lifetime; Fluorescence Anisotropy
Kỹ thuật phân tích huỳnh quang
Keywords: Fluorescence spectroscopy,Phép đo phổ, huỳnh quang,Spectrometry, Fluorescence,Huỳnh quang phổ; Phương pháp,Methods